Capacity Building for Fishermen’s Wives Towards Food Sovereignty at Cemara Beach, Banyuwangi Regency - Akbar Sandi Wijaya; Putri Istianingrum; Shinta Hiflina Yuniari; Ervina Wahyu Setyaningrum (International Journal of Community Service Learning, 2025)
Food sovereignty, which has become a global issue, is a solution in improving welfare, especially among fishermen. Towards food sovereignty, capacity building is needed, in this case fishermen's wives who contribute to this, because their abilities exceed the fishermen themselves, especially in managing households and alternative livelihoods. The purpose of this community service is to increase the capacity of fishermen's wives through verticulture, hydroponics, aquaponics, and catfish cultivation by utilizing used gallons, towards food sovereignty. The subjects in this activity are the wives of coastal fishermen at Cemara Beach, Banyuwangi District, Banyuwangi Regency. The method used is Participatory Rural Appraisal (PRA), which is the process of entering the service location (Getting in), then being at the location (Getting Along), and recording data. The results obtained are that the capacity building of fishermen's wives in Pantai cemara is carried out through empowerment programs in the form of several trainings such as verticulture, hydroponics, aquaponics, and catfish cultivation using used gallons. Where the results of the training produce a product that can lead to food sovereignty, it also helps fishermen's households, especially in improving family health and welfare.